Peran Karakteristik Wirausahawan dalam Entrepreneurial Marketing di UMKM Kebun Sehat JSR - Zahra, Hanun; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
In its development, MSMEs face many challenges in marketing products. This requires the use of digital tools such as social media to support their marketing activities. However, limited MSME resources require entrepreneurial marketing approach that suits the characteristics of MSMEs. One of the MSMEs that uses social media to market its products creatively and innovatively is Kebun Sehat JSR. However, there was a decline in product sales after COVID-19 pandemic. The characteristics of entrepreneurs play an important role in facing challenges and market changes such as those experienced by Kebun Sehat JSR with a decline in sales after COVID-19 pandemic. Recent research in this field has emphasized the importance of entrepreneurial characteristics in adopting entrepreneurial marketing in MSMEs. Therefore, this study aims to determine the role of entrepreneurial characteristics in entrepreneurial marketing at Kebun Sehat JSR. This study uses a qualitative method with thematic analysis. Data were obtained through interviews and observations. Analyzed using NVivo 12 Plus. Based on the results, it can be concluded that the entrepreneur characteristics play a role in entrepreneurial marketing in MSMEs with four characteristics including, seeing market opportunities, being proactive about market changes, daring to take risks, and being consistent in maintaining the vision.